Android-Based Media for Enhancing Critical Thinking in Elementary Science: A Systematic Review - M. Jazuri; Mintarsih Arbarini; Bambang Subali; Nuni Widiarti (Research, Training and Philanthropy Institution Natural Aceh, 2026)
The rapid advancement of information technology has accelerated innovation in learning media, particularly in elementary science education where developing higher-order thinking is critical. This PRISMA-guided systematic literature review examines the effectiveness of Android-based learning media in enhancing elementary students’ critical thinking. Twenty-five peer-reviewed articles published between 2020 and 2025 were selected from Google Scholar, SINTA, and Scopus. Included studies comprised quantitative, qualitative, and mixed methods designs and were appraised for quality. Findings show that Android-based media, including educational games, interactive multimedia, augmented reality applications, and e-modules generally improve engagement and learning outcomes. However, only about one third of the studies explicitly measured critical thinking indicators such as analysis, evaluation, and problem solving, revealing a persistent gap between technological innovation and cognitive assessment. The review highlights pedagogical integration, offline access, and teacher readiness as key factors. Overall, Android-based media present a flexible, accessible option for 21st-century elementary science education with implications for instructional design, policy, and future research.